CRYSTAL CHEMICAL CONTROLS ON RARE EARTH ELEMENT PARTITIONING BETWEEN EPIDOTE-GROUP MINERALS AND MELTS: AN EXPERIMENTAL AND THEORETICAL STUDY - Frei D.; Liebscher A.; Wittenberg A.; Shaw C.S.J. (My University, 2003)
We have experimentally determined the partitioning of REE (rare earth elements) between zoisite and hydrous silicate melt at 1,100 °C and 3 GPa. All REE behave moderately compatible in zoisite with respect to the melt and all % MathType!MTEF!2!1!+- % feaafeart1ev1aaatCvAUfeBSn0BKvguHDwzZbqefeKCPfgBGuLBPn % 2BKvginnfarmWu51MyVXgatuuDJXwAK1uy0HwmaeHbfv3ySLgzG0uy % 0Hgip5wzaebbnrfifHhDYfgasaacH8srps0lbbf9q8WrFfeuY-Hhbb % f9v8qqaqFr0xc9pk0xbba9q8WqFfea0-yr0RYxir-Jbba9q8aq0-yq % -He9q8qqQ8frFve9Fve9Ff0dmeaabaqaciGacaGaaeqabaWaaeWaea % aakeaacaWGebWaa0baaSqaaiaadkfacaWGfbGaamyraaqaaiaadQha % caWGVbGaai4laiaad2gacaWGLbGaamiBaiaadshaaaaaaa!4345! $$ D_{REE}^{zo/melt} $$ show a smooth parabolic dependence on ionic radius. The partitioning parabola peaks at Nd % MathType!MTEF!2!1!+- % feaafeart1ev1aaatCvAUfeBSn0BKvguHDwzZbqefeKCPfgBGuLBPn % 2BKvginnfarmWu51MyVXgatuuDJXwAK1uy0HwmaeHbfv3ySLgzG0uy % 0Hgip5wzaebbnrfifHhDYfgasaacH8srps0lbbf9q8WrFfeuY-Hhbb % f9v8qqaqFr0xc9pk0xbba9q8WqFfea0-yr0RYxir-Jbba9q8aq0-yq % -He9q8qqQ8frFve9Fve9Ff0dmeaabaqaciGacaGaaeqabaWaaeWaea % aakeaadaqadaqaaiaadseadaqhaaWcbaGaamOtaiaadsgaaeaacaWG % 6bGaam4Baiaac+cacaWGTbGaamyzaiaadYgacaWG0baaaOGaeyypa0 % JaaGinaiaac6cacaaI5aaacaGLOaGaayzkaaaaaa!4762! $$ \left( {D_{Nd}^{zo/melt} = 4.9} \right) $$, and the compatibility slightly decreases towards La % MathType!MTEF!2!1!+- % feaafeart1ev1aaatCvAUfeBSn0BKvguHDwzZbqefeKCPfgBGuLBPn % 2BKvginnfarmWu51MyVXgatuuDJXwAK1uy0HwmaeHbfv3ySLgzG0uy % 0Hgip5wzaebbnrfifHhDYfgasaacH8srps0lbbf9q8WrFfeuY-Hhbb % f9v8qqaqFr0xc9pk0xbba9q8WqFfea0-yr0RYxir-Jbba9q8aq0-yq % -He9q8qqQ8frFve9Fve9Ff0dmeaabaqaciGacaGaaeqabaWaaeWaea % aakeaadaqadaqaaiaadseadaqhaaWcbaGaamitaiaadggaaeaacaWG % 6bGaam4Baiaac+cacaWGTbGaamyzaiaadYgacaWG0baaaOGaeyypa0 % JaaG4maiaac6cacaaI5aaacaGLOaGaayzkaaaaaa!475C! $$\left( {D_{La}^{zo/melt} = 3.9} \right)$$ and decreases by half an order of magnitude towards Yb % MathType!MTEF!2!1!+- % feaafeart1ev1aaatCvAUfeBSn0BKvguHDwzZbqefeKCPfgBGuLBPn % 2BKvginnfarmWu51MyVXgatuuDJXwAK1uy0HwmaeHbfv3ySLgzG0uy % 0Hgip5wzaebbnrfifHhDYfgasaacH8srps0lbbf9q8WrFfeuY-Hhbb % f9v8qqaqFr0xc9pk0xbba9q8WqFfea0-yr0RYxir-Jbba9q8aq0-yq % -He9q8qqQ8frFve9Fve9Ff0dmeaabaqaciGacaGaaeqabaWaaeWaea % aakeaadaqadaqaaiaadseadaqhaaWcbaGaamywaiaadkgaaeaacaWG % 6bGaam4Baiaac+cacaWGTbGaamyzaiaadYgacaWG0baaaOGaeyypa0 % JaaGymaiaac6cacaaIXaaacaGLOaGaayzkaaaaaa!4760! $$\left( {D_{Yb}^{zo/melt} = 1.1} \right)$$. Application of the elastic strain model of Blundy and Wood (1994) to the available zoisite and allanite REE mineral/melt partitioning data and comparison with partitioning pattern calculated from a combination of structural and physical data (taken from the literature) with the elastic strain model suggest that in zoisite REE prefer the A1-site and that only La and Ce are incorporated into the A2-site in significant amounts. In contrast, in allanite, all REE are preferentially incorporated into the large and highly co-ordinated A2 site. As a result, zoisite fractionates the MREE effectively from the HREE and moderately from the LREE, while allanite fractionates the LREE very effectively from the MREE and HREE. Consequently, the presence of either zoisite or allanite during slab melting will lead to quite different REE pattern in the produced melt.
Keywords: zoisite